2020
DOI: 10.51200/ljms.v14i.2868
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges of Waqf Practice in Malaysia: A Review

Abstract: The literature of waqf is no longer foreign in the body of knowledge. Many researchers have written about waqf in various settings and disciplines. One of the waqf subjects studied was on the issues and challenges faced in practising waqf. The objectives of this study are to review and formulate issues and challenges of waqf practices in Malaysia that have been recorded by previous researchers. Using the content analysis method, past studies have been grouped and formulated. As a result, the study found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…Nor and Rosman (2017) found that the community is hesitant when it comes to implementing waqf education for higher education institutions in Malaysia because of lack of knowledge of waqf as well as waqf governance that has not been properly implemented. Waqf land was also challenging to be developed because of non-strategic location (Mutalib et al, 2019) and not properly maintained (Jalil, 2020). In terms of corporate waqf, it was found that attitude and subjective norm have a positive relationship toward the behavioral intention.…”
Section: Intention Of Small-medium Enterprises' Ownersmentioning
confidence: 99%
“…Nor and Rosman (2017) found that the community is hesitant when it comes to implementing waqf education for higher education institutions in Malaysia because of lack of knowledge of waqf as well as waqf governance that has not been properly implemented. Waqf land was also challenging to be developed because of non-strategic location (Mutalib et al, 2019) and not properly maintained (Jalil, 2020). In terms of corporate waqf, it was found that attitude and subjective norm have a positive relationship toward the behavioral intention.…”
Section: Intention Of Small-medium Enterprises' Ownersmentioning
confidence: 99%
“…It is easy to manage, more practical to distribute, still able to generate more funds and relevant means for the development of the society (Nadwi & Kroessin, 2013;Saduman & Aysun, 2009;Kahf, 1999). Cash waqf is used to finance various activities, for instance education, constructing school, hospital, bridge, roads, ports, mosque maintenance, social services, clean water and workers (Jalil, 2020;Johari et al, 2015;Mohsin, 2009;Cizakca 2013). Furthermore, we would like to offer the cash waqf model that is able to apply among OIC country members in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Dan, bertakwalah kepada Allah, sesungguhnya Allah Maha Penerima Tobat Lagi Maha Penyayang." Sedangkan perilaku menemukan dan melaksanakan solusi terbaik tercantum dalam surat Ali Imran ayat 92 (Ismail, 2015) yang berbunyi "Kamu sekali-kali tidak sampai kepada kebajikan (yang sempurna), sebelum kamu menafkahkan (mempersembahkan) sesuatu yang kamu cintai. Dan apa saja yang kamu nafkahkan, maka sesungguhnya Allah mengetahuinya.…”
Section: Sinergiunclassified